Pollinators, pests and yield—Multiple trade‐offs from insecticide use in a mass‐flowering crop. Issue 9 (21st July 2022) - Knapp, Jessica L.; Bates, Adam; Jonsson, Ove; Klatt, Björn; Krausl, Theresia; Sahlin, Ullrika; Svensson, Glenn P.; Rundlöf, Maj
Abstract: Multiple trade‐offs likely occur between pesticide use, pollinators and yield (via crop flowers) in pollinator‐dependent, mass‐flowering crops (MFCs), causing potential conflict between conservation and agronomic goals. To date, no studies have looked at both outcomes within the same system, meaning win‐win solutions for pollinators and yield can only be inferred. Here, we outline a new framework to explore these trade‐offs, using red clover ( Trifolium pratense ) grown for seed production as an example. Specifically, we address how the insecticide thiacloprid affects densities of seed‐eating weevils ( Protapion spp.), pollination rates, yield, floral resources and colony dynamics of the key pollinator, Bombus terrestris . Thiacloprid did not affect the amount of nectar provided by, or pollinator visitation to, red clover flowers but did reduce weevil density, correlating to increased yield and gross profit. In addition, colonies of B. terrestris significantly increased their weight and reproductive output in landscapes with (compared with without) red clover, regardless of insecticide use. Synthesis and applications . We propose a holistic conceptual framework to explore trade‐offs between pollinators, pesticides and yield that we believe to be essential for achieving conservation and agronomic goals. This framework applies to all insecticide‐treated mass‐flowering crops (MFCs) and can be adapted to include other ecological processes. Trialling the framework in our study system, we found that our focal insecticide, thiacloprid, improved red clover seed yield with no detected effects on its key pollinator, B. terrestris, and that the presence of red clover in the landscape can benefit pollinator populations. Abstract : We propose a holistic, conceptual framework to explore trade‐offs between pollinators, pesticides and yield that we believe to be essential for achieving conservation and agronomic goals. This framework applies to all insecticide‐treated mass‐flowering crops (MFCs) and can be adapted to include other ecological processes. Trialling the framework in our study system, we found that our focal insecticide, thiacloprid, improved red clover seed yield with no detected effects on its key pollinator, Bombus terrestris, and that the presence of red clover in the landscape can benefit pollinator populations.